Radiography of Clavicula Os with Suspected Avulsion Fracture in Advent Medan General Hospital - Tarigan, Liberti; Sidauruk, Juliana Lasniar (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The clavicle is an S-shaped bone that articulates laterally with the acromioma process of the scapula, medially with the manubrium of the clavicular notch to form the clavicular joint. An avulsion fracture is a disconnection of the clavicle bone caused by direct and indirect trauma in the position of the arm being cut off or pulled out (outstretched hand) because the trauma continues from the wrist to the clavicle. Radiography is an appropriate method to show abnormalities in the os calvicula. The aim is to show the anatomy of the clavicle bone and its abnormalities. This examination uses the Antero-Posterior projection. The X-ray aircraft used is GE with a capacity of 500 mA. The tape used is 30 cm x 40 cm. Processing film used is Computed Radiography.